Development Of A Circulation Library System(Case Study Of T.Y Danjuma Library - Acu) (International Journal of Engineering and Computer Science, 2015)
In order to achieve an easier method of book circulation in libraries, designed and implemented circulation managementsystems are being pushed as a replacement for the conventional library cards. Library cards can be easily tampered with, lost or passed on toanother student. Therefore, automated circulation management system will provide a centralized database of books and management oflibrary circulation activities. This project is intended to have a database where data about the books in the library will be stored and newarrivals will also be registered. Names of students that intend to borrow books in the library will be registered in the circulation system andduration of lease of books would be included. The project aims at automating (designing and implementing) the circulation unit of thelibrary using the T.Y.Danjuma Library of AjayiCrowther University as case study.